2019
DOI: 10.1016/j.seizure.2019.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with seizure-related motor vehicle accidents among patients with epilepsy in West China

Abstract: This study was conducted to investigate the relevant demographics and clinical factors contributing to seizure-related motor vehicle accidents in west China. Methods: All driving patients who visited our epilepsy clinic in the West China Hospital, between October 2012 and October 2016, were invited to participate. Data on social demographics, clinical features, and motor vehicle accidents were collected during structured interviews. Binary logistic regression was used to identify factors associated with seizur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…In this nomogram model, the seizure-free interval, seizure types, aura, whether seizures only occur nocturnally, age, and marriage are all factors related to traffic accidents. Our previous study showed that the frequency of seizure and seizure types can be risk factors for traffic accidents [12]. Our studies reached a similar conclusion (Frequency less than 1 year, RR 0.73) with a previous study [4,[19][20][21][22].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this nomogram model, the seizure-free interval, seizure types, aura, whether seizures only occur nocturnally, age, and marriage are all factors related to traffic accidents. Our previous study showed that the frequency of seizure and seizure types can be risk factors for traffic accidents [12]. Our studies reached a similar conclusion (Frequency less than 1 year, RR 0.73) with a previous study [4,[19][20][21][22].…”
Section: Discussionsupporting
confidence: 91%
“…Few studies mention whether seizures only occur nocturnally. Li et al stated that seizure only at night might be a potential protective factor (10.3% vs 24.0%, p = 0.05) [12], although there was no prominent significant difference.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This was comparable to a Chinese study in 2019, where seizure freedom of more than 2 years was associated with an 89% reduced chance of a RTA. 6 Attempts have been made in the past to stratify driving risk based on levels of seizure related impairments. The common SLJoN ⏐ BOTEJU et al belief was that aura provided sufficient warning of a seizure.…”
Section: Discussionmentioning
confidence: 99%
“…4 Driving by those with epilepsy is reported from many non-Western countries as well. These include Saudi-Arabia 5 , China 6 , and India 7 , where the rates of RTAs are 27%, 7.5% and 7.8% respectively. A single previous study from Sri Lanka reported an accident rate of 15%.…”
Section: Introductionmentioning
confidence: 99%